PERAN OPERATOR SEKOLAH DALAM MEMAKSIMALKAN FUNGSI SISTEM DAPODIK UNTUK ADMINISTRASI PENDIDIK DAN TENAGA KEPENDIDIKAN DI TK LITTLE ABDULLAH SCHOOL CILEGON - Hadzar Nur Ikhram; Umalihayati; Mohamad Bayi Tabrani (STKIP Subang, 2026)
This research aims to understand the role of school operators in optimizing the use of the Basic Education Data System (Dapodik) for the administration of educators and education personnel at Little Abdullah School Cilegon Kindergarten. The Basic Education Data System (Dapodik) is a system that manages education data nationally, assisting the planning and evaluation of education programs. The method used is descriptive qualitative through interviews, observation and documentation. The results show that school operators play an important role in entering, updating and reporting data. Challenges faced include a lack of understanding of Dapodik features, time constraints and technical issues. Proposed solutions include regular training and increased technical support. The conclusion shows that the role of school operators is crucial in maximizing the functions of the Basic Education Data System (Dapodik) for better education administration.